Penerapan Model Pembelajaran Student Team Achievement Division - Juniarti Pasessha Putri; Asep Sukenda Egok; Aren Frima (Journal of Elementary School (JOES), 2023)
This study aims to determine the complete social studies learning outcomes of Grade IV students at SD Negeri 31 Lubuklinggau after implementing the Student Team Achievement Division (STAD) learning model. This research method uses a quasi-experimental research method. The population and sample are Grade IV students with a total of 28 students. Data collection technique is done by testing technique. The data analysis technique used the z-test at a significant level (α = 0.05). The results showed that z count 5.31 ≥ z table 1,64, so it can be concluded that social studies learning outcomes of Grade IV students at SD Negeri 31 Lubuklinggau after the application of the Student Team Achievement Division (STAD) learning model were significantly completed with an average student learning outcome of 81 ,1. Keywords: Student Team Achievement Division (STAD) Model, Learning Outcomes, Social Sciences